2001
DOI: 10.1021/ie010019q
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Iron Additives for Advanced Control of NOx Emissions from Stationary Combustion Sources

Abstract: A novel NO x control technique based on the utilization of iron-containing compounds was studied. Iron-containing additives can be injected in small amounts either into the combustion zone or, if reburning is used, into the reburning zone to reduce NO x emissions. Tests in a 300-kW Boiler Simulator Facility demonstrate that iron additives achieve 20−30% NO x reduction without reburning, whereas in conjunction with reburning, they increase NO x reduction from about 60%, typical for conventional reburning, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 32 publications
(44 reference statements)
0
30
0
Order By: Relevance
“…4, favorable conditions for the utilization of iron in the de-NO x process are created in fuel-rich atmospheres. Lissianski et al [9] reported a similar trend using a pilot-scale boiler system. The pulverized coal and natural gas were used as the main fuel.…”
Section: Methodsmentioning
confidence: 70%
See 4 more Smart Citations
“…4, favorable conditions for the utilization of iron in the de-NO x process are created in fuel-rich atmospheres. Lissianski et al [9] reported a similar trend using a pilot-scale boiler system. The pulverized coal and natural gas were used as the main fuel.…”
Section: Methodsmentioning
confidence: 70%
“…The influence of the aforementioned reaction on the NO conversion was intentionally omitted to emphasize the role of iron as an additive that supports the reburning process. The experiments were performed this way because the influence of temperature, reburning fuel type, reburning fuel heat input and other process parameters on the efficiency of NO reduction has already been intensively investigated [30][31][32][33], whereas relatively few studies on the influence of iron on the reburning efficiency have been published [9,14,23,24]. The efficiency of NO x reduction in the presence of iron as a function of the excess air numbers was calculated according to Eq.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations